(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
This article discusses the lapar genre typical of Khorezm folklore. It is about the lexical-semantic features of the units of reference found in the composition of the words.